INFLUENCE OF FLEET MANAGEMENT OUTSOURCING ON SERVICE DELIVERY PERFORMANCE IN NAIROBI BOTTLERS LIMITED - Imbuga, Adrian; Guyo, Dr. Wario (International Journal of Supply Chain Management, 2018)
Purpose: The main aim of the study was to establish the influence of fleet management outsourcing on service delivery performance at Nairobi Bottlers Limited. Methodology: The study used a case study research design. Bryman (2008) writes that a case study is a research design that entails comprehensive detailing and intensive analysis of a single case. Data was collected from senior managers and staff at NBL using structured close-ended questionnaires. The questionnaires were administered on a drop and collect later basis to seventy respondents (staff at NBL). Data was processed using SPSS, and multiple regression analysis was applied to establish the influence of the four independent variables of the study on service delivery performance, which is the dependent variable. The results were presented in tables. Results: The findings obtained show that acquisition of new fleet positively impacts on operational efficiency besides boosting employee morale which has a subsequent contribution on service delivery performance. In addition, when the maintenance of fleet is outsourced, service delivery performance is enhanced through timely delivery of products. Policy recommendation: The study recommends that a hybrid approach is a viable model to adopt. A hybrid model would involve an internal fleet management role working with an outsourced fleet management firm, so that a firm gains from the benefits associated with each of the independent models.